Impact of foreign players’ participation in the Palestinian basketball league on team cohesion from the perspective of local players - Yousef, Iyad A.; Kayed, Mahmoud W.; Liftawi, Sana M. (Frontiers in Psychology, 2025)
ObjectiveThe purpose of this paper is to assess the impact of foreign players’ participation in the Palestinian Basketball League on team cohesion from the perspective of local players.MethodsUsing a descriptive-analytical method, the researchers developed a cohesion measurement tool with three dimensions: psychological, social, and team belonging. The tool comprised 30 items, equally distributed across the dimensions, based on player status, experience, and position. The study surveyed 84 players aged between 18 and 38 in the Palestinian Basketball League.ResultsThe findings revealed that cohesion was rated as moderate (mean = 3.32), with higher scores in team affiliation (3.50) compared to psychological cohesion (3.21). Experience-based differences showed that players with less than 5 years and more than 10 years of experience exhibited higher cohesion levels compared to those with 6–10 years. Positional differences favored forwards and guards. Regarding player status, reserve players demonstrated higher cohesion in the psychological and team belonging dimensions, although no significant differences were found in the social dimension.ConclusionThe study concludes that foreign players have a positive impact on team cohesion, and it was rated as moderate with higher scores in team affiliation compared to psychological cohesion. The researchers recommend careful selection of foreign players to enhance team cohesion and stability. This study contributes to the understanding of foreign players’ role in fostering team dynamics and performance in the Palestinian Basketball League, expanding the literature on the topic. This study is original and valuable, as there has been almost no previous research that has measured and evaluated the impact of foreign players’ participation in the Palestinian basketball league on team cohesion from the perspective of local players.